From Chaotic Classrooms to Student Anxiety: The Hidden Toll of Unqualified Teaching Observation of Early Childhood Education and Elementary Schools - Husnul Khotimah, Annisa (LPPM Universitas Mohammad Husni Thamrin, 2025)
This study examines the impact of non-certified and unprepared instructional staff on the quality of education and student well-being within educational institutions. Through a synthesis of student testimonials, supervisor account, and educator reflections, the research identifies a significant correlation between a lack of professional teacher certification and systemic instructional failure. The findings reveal that pedagogical incompetence frequently results in poor classroom management, chaotic learning environments, and the inability to meet core curriculum objectives. Furthermore, the data indicates that uncertified teachers often lack the developmental insight necessary to support students' psychological and emotional needs, leading to increased student anxiety. The study also highlights broader systemic consequences, including the overburdening of teacher mentors, fragmented team collaboration, and increased financial pressure on parents to seek supplemental tutoring due to mismatched teacher expertise. Ultimately, these narratives underscore that professional certification is a vital prerequisite for effective, empathetic education. The study concludes that prioritizing the recruitment of qualified, credentialed educators is essential to maintaining institutional standards and ensuring equitable, high-quality learning outcomes for all students.